2013
DOI: 10.2106/jbjs.l.01014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Native Anatomy with Recommended Safe Component Orientation in Total Hip Arthroplasty for Primary Osteoarthritis

Abstract: The present findings of native acetabular and femoral orientation in patients with primary hip osteoarthritis support intraoperative component positioning for total hip arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 31 publications
5
45
0
2
Order By: Relevance
“…15,25,26 In addition, a more proximal knee joint would cause the pelvis to increase forward tilt during the heelstrike phase of gait, 27 an established cause of hip osteoarthritis. [28][29][30][31][32][33] Song et al 15 showed increased mechanical work during gait for patients with limb-length discrepancies >3 cm, perhaps by a similar mechanism, decreasing the distance between the knee and hip joint relative to the distance between the knee and ankle joint.…”
Section: Discussionmentioning
confidence: 99%
“…15,25,26 In addition, a more proximal knee joint would cause the pelvis to increase forward tilt during the heelstrike phase of gait, 27 an established cause of hip osteoarthritis. [28][29][30][31][32][33] Song et al 15 showed increased mechanical work during gait for patients with limb-length discrepancies >3 cm, perhaps by a similar mechanism, decreasing the distance between the knee and hip joint relative to the distance between the knee and ankle joint.…”
Section: Discussionmentioning
confidence: 99%
“…The normative values of the inclination and anteversion angles in our study differ significantly from those employed for the anterior pelvic plane and other planes used in the literature [25][26][27]. Hence, it is necessary to establish norms for the sacrum base plane to enable its further use in future studies.…”
Section: Wnioskimentioning
confidence: 67%
“…czy Murtha ze wsp., wykorzystując inne płaszczyzny odniesienia [4,[6][7][8]. Uzyskane wartości normatywne kątów inklinacji i antewersji róż nią się znacząco od tych, stosowanych dla płasz czyzny miednicznej przedniej (Anterior Pelvic Pal ne) oraz innych stosowanych w literaturze płasz czyzn [25][26][27]. Stąd istnieje konieczność wyznaczenia norm dla płasz czyzny podstawy kości krzyżowej, w celu umożliwienia jej dalszego stosowania w przyszłości.…”
Section: Discussionunclassified
“…Beside Lewinnek's Bsafe zone^of cup inclination between 30 degrees and 50 degrees and cup anteversion between 5 degrees and 25 degrees [1], we chose eight currently available standard rules of combined anteversion [3][4][5][6][7][20][21][22] and assessed whether the component position of each patient was Table 2. For each definition of combined anteversion gait parameters and clinical scores were compared between patients with combined cup and stem anteversion according to the corresponding combined anteversion rule and patients with combined component anteversion outside the combined anteversion benchmarks as measured on 3D-CT in the supine position.…”
Section: Methodsmentioning
confidence: 99%